The Development of Welfare Politics of the Dutch East Indies in 1900-1918 - Radhitya Eka Widjanarko; Muhammad Nurun Alanur; Muhammad Iqbal Birsyada (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
This article writing to: (1) Explain how the Dutch East Indies political system is, (2) Analyze how ethical politics is in the archipelago (Indonesia), (3) Analyze how the political system is ethical and eastern towards Islam, and explain the Ordinance Policy towards Islamic Religion Teachers by the Dutch East Indies, (4) Explain how the failure of ethical politics can occur. The author in writing article applied historical research method with consist of collecting sources, critism source, intepretation, and historiograph. Results of this writing article indicate that: (1) Ethic politic policies implemented on the Duutch East indie were based on the desire of liberals in the Netherlands to prosper in the colonized country, (2) East-west politics in Islam caused Muslims to want to break away from the Dutch defense, (3) Ordinance Policy on Islamic Religion Teachers by the Dutch East Indies Government, (4) The political failure was motivated by the many reactions to the implementation of ethical politics, the Dutch got big profits but inversely the welfare of the people was low.